Soft Tribology and Its Relationship With the Sensory Perception in Dairy Products: A Review - Corvera-Paredes, Beatriz; Sánchez-Reséndiz, Aidee I.; Medina, Dora I.; Espiricueta-Candelaria, Rosa S.; Serna-Saldívar, Sergio; Chuck-Hernández, Cristina (Frontiers in Nutrition, 2022)
Nowadays, dairy products, especially fermented products such as yogurt, fromage frais, sour cream and custard, are among the most studied foods through tribological analysis due to their semi-solid appearance and close relationship with attributes like smoothness, creaminess and astringency. In tribology, dairy products are used to provide information about the friction coefficient (CoF) generated between tongue, palate, and teeth through the construction of a Stribeck curve. This provides important information about the relationship between friction, food composition, and sensory attributes and can be influenced by many factors, such as the type of surface, tribometer, and whether saliva interaction is contemplated. This work will review the most recent and relevant information on tribological studies, challenges, opportunity areas, saliva interactions with dairy proteins, and their relation to dairy product sensory.